Anti-Terrorism Education Curriculum in an Effort to Prevent the Development of Terrorism Ideology in Indonesia - Dhanu Prahara; Stanislaus Riyanta; Amanah (South Sulawesi Education Development (SSED), 2025)
This research aims to describe the problem based on a literature review regarding efforts to prevent terrorism through anti-terrorism education in Indonesia. The method used in the research is a qualitative method. The literature review in this research was carried out by collecting, reading, analyzing and understanding existing sources of information to be used as references in writing articles. The objects discussed in the research are teenagers in the ideology of terrorism, the role of schools in efforts to prevent the ideology of terrorism and strategies for preventing terrorism in the world of education in Indonesia. The steps in research are choosing a topic that will be material for research, searching for information, collecting information from various data sources, preparing to present data, and finally preparing a report. The research results are in the form of a description that forms of terrorism in education are not all acts of violence, but can also be manifested in the form of speech and attitudes that have the potential to give rise to violence. The government instills the Pancasila ideology completely and evenly in the world of education in Indonesia, by implementing an independent curriculum, which contains the profile of Pancasila students.